2009
DOI: 10.1111/j.1540-8191.2008.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Open Heart Surgery in Patients with End-Stage Renal Failure: Fifteen-Year Experience

Abstract: Open heart surgery in hemodialysis patients is associated with a higher incidence of risks, but can be performed with acceptable operative complications and mortality with an effective hemodialysis program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In our view, this is of paramount importance and can not been analyzed in detail yet. Although factors predisposing to low cardiac output syndrome (LCOS) have been described, the etiology of LCOS after heart surgery still remains somewhat obscure [2,11]. Remarkably, a low cardiac output in our study constituted a high risk manifestation, exceeding the importance of "surgical" complications such as prolonged cross-clamping times and redo operations.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…In our view, this is of paramount importance and can not been analyzed in detail yet. Although factors predisposing to low cardiac output syndrome (LCOS) have been described, the etiology of LCOS after heart surgery still remains somewhat obscure [2,11]. Remarkably, a low cardiac output in our study constituted a high risk manifestation, exceeding the importance of "surgical" complications such as prolonged cross-clamping times and redo operations.…”
mentioning
confidence: 55%
“…Although satisfactory results have been achieved according to the recent literature, higher complication and mortality rates have been simultaneously reported in octogenarians compared to younger patients [1]. Considerable concerns remain about the role of coexisting renal failure and neurological complications [2]. A higher surgical complexity in octogenarians has been reported in a study which included 641 patients over 80 years of age.…”
mentioning
confidence: 99%
“…The first involves preoperative undernutrition, anemia, electrolyte abnormalities, bleeding tendency, and decreased immune function [6][7][8][9][10][11][12][13]. In the present study, preoperative cardiac comorbidity factors included angina pectoris and myocardial infarction, and were seen at a high frequency in 8 of the 21 patients (38%).…”
Section: Discussionmentioning
confidence: 83%
“…heart surgery versus those with normal functioning kidneys. [6] Novel operative techniques and preoperative management are necessary for favorable surgical and long-term outcomes. [7,8] In order to obtain positive surgical results, special attention should be given to problems such as fluid and electrolyte imbalance, improper hemodynamics, and bleeding at each period of the operation.…”
Section: Resultsmentioning
confidence: 99%
“…[12,13] However, when CABG was combined with valve replacement, the ratio declined to 70%, [14] and five-year survival rates have been chronicled as low as 20%. [6] Furthermore, the reported hospital mortality rates have ranged between 0 and 20%. [13,15] Durmaz et al [16] showed that prophylactic dialysis might decrease postoperative morbidity and mortality, and they reported a 12.5% hospital mortality rate along with a 75% complication rate.…”
Section: Resultsmentioning
confidence: 99%